Febrile Proteinuria in Hospitalized Children: Characterization of Urinary Proteins - Gurevich, Evgenia; Israel, Eytan; Segev, Yael; Landau, Daniel (Frontiers in Pediatrics, 2018)
Background: Transient proteinuria during febrile illness is a common phenomenon. Recent studies have re-examined the pathophysiology of proteinuria and new urinary markers to characterize it, including B7-1 (CD80), which is expressed also in glomerular podocytes and influences the glomerular barrier. Aim: To investigate the pattern of proteinuria in febrile non-renal diseases, including B7-1. Methods: We prospectively analyzed urine samples of 44 febrile children and 28 afebrile controls for different protein components: albumin (glomerular marker), β2-microglobulin (tubular marker), uromodulin (Tamm Horsfall protein- THP, a renal endogenous protein) and B7-1. Febrile illness was characterized as focal bacterial versus viral. Exclusion criteria were underlying renal disease, steroid treatment or urinary tract infection. Results: Elevated urine albumin (64.5±10.3 versus 17.8±4mg/g, mean ± S.E.M., p=0.0009) and β2-microglobulin (1.44±0.34 versus 0.182±0.03mg/g, mean ± S.E.M., p=0.005] and decreased uromodulin (10.5±1 vs 26.7±2.2 Arbitrary units, mean ± S.E.M., p=0.0001) excretion were found during febrile illness versus controls. Urine B7-1 was also increased in the febrile group (0.27±0.05 versus 0.07±0.01ng/ml, mean ± S.E.M., p=0.001), and was the only marker which was significantly higher in bacterial versus viral disease. Conclusions: Febrile proteinuria is not generalized: while proteins of both glomerular and tubular origin increase, uromodulin decreases. Urine B7-1 is increased during fever, more significantly in bacterial infections. Thus, urinary B7-1 may be used as an additional marker to differentiate between febrile states of bacterial versus viral origin.